Intervention Using Visual-Scaffolding Nahw Grammar Charts A Quasi-Experimental Study on I‘rāb Accuracy and Sentence Structure in Pesantren - Hanafi, Deva; Sunarko, Asep; Zuhdi, Ahmad (Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2026)
This study aims to examine the effectiveness of a visual-scaffolding-based Nahwu formula chart intervention on students’ grammatical ability. Using a quantitative, quasi-experimental design (One-Group Pretest-Posttest Design), this study involved 30 students at Fatkhul Mu’in Ali Masykur Islamic Boarding School in Wonosobo as research subjects. Data collection techniques included tests, treatment, observation, and documentation. The results of the study show a significant increase in the average scores. The lowest student score improved from 38 to 63, while the highest score reached 96. The effectiveness analysis using the N-Gain score yielded a moderate value. These findings confirm that the use of formula charts as a visual instrument can reduce students’ cognitive load and facilitate pattern recognition in Arabic syntactic analysis. This study recommends the integration of visual media into the ilmu alat curriculum in Islamic boarding schools to accommodate the learning styles of contemporary students.